2014
DOI: 10.1089/apc.2014.0171
|View full text |Cite
|
Sign up to set email alerts
|

Shame, Guilt, and Stress: Community Perceptions of Barriers to Engaging in Prevention of Mother to Child Transmission (PMTCT) Programs in Western Kenya

Abstract: While global scale-up of prevention of mother-to-child transmission of HIV (PMTCT) services has been expansive, only half of HIV-infected pregnant women receive antiretroviral regimens for PMTCT in subSaharan Africa. To evaluate social factors influencing uptake of PMTCT in rural Kenya, we conducted a community-based, cross-sectional survey of mothers residing in the KEMRI/CDC Health and Demographic Surveillance System (HDSS) area. Factors included referrals and acceptability, HIV-related stigma, observed disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 38 publications
4
47
1
Order By: Relevance
“…Gender power dynamics likely also impact HIV risk behaviors independently of individual motivation and behavior. 18,[37][38][39] Our findings suggested that women gained power in the relationship by having children, perhaps by legitimizing the union with biological children desired by male partners. Women uncertain about conception described raising concerns regarding pregnancy and HIV risk with their partners, but ultimately the couples' decision to conceive conceded to the male partners' desires.…”
Section: Discussionmentioning
confidence: 70%
“…Gender power dynamics likely also impact HIV risk behaviors independently of individual motivation and behavior. 18,[37][38][39] Our findings suggested that women gained power in the relationship by having children, perhaps by legitimizing the union with biological children desired by male partners. Women uncertain about conception described raising concerns regarding pregnancy and HIV risk with their partners, but ultimately the couples' decision to conceive conceded to the male partners' desires.…”
Section: Discussionmentioning
confidence: 70%
“…Research has shown that relevant community perceptions explain why women may be unwilling to take ART including HIV-related stigma, guilt, lack of knowledge, denial, stress and despair or futility. Maternal depression and internalisation of HIV-related stigma, while situated at the individual level, have been shown to further decrease uptake of treatment 54. A literature review18 highlights that while much has been written about how child-specific factors (eg, psychosocial function, neurological development, development stage) and regimen characteristics (eg, drug formulation, changes to treatment plans) may affect children's ART adherence, little is known about social factors impacting children's ART adherence 55…”
Section: Methodsmentioning
confidence: 99%
“…Maternal depression and internalisation of HIV-related stigma, while situated at the individual level, have been shown to further decrease uptake of treatment. 54 A literature review 18 highlights that while much has been written about how child-specific factors (eg, psychosocial function, neurological development, development stage) and regimen characteristics (eg, drug formulation, changes to treatment plans) may affect children's ART adherence, little is known about social factors impacting children's ART adherence. 55 ▸ Social support has been shown to enhance adherence to HIV medication, with practical support bearing the highest correlation.…”
Section: Case Selectionmentioning
confidence: 99%
“…112,113 Prevailing stigma and discrimination against HIV and weak maternal child health services hampered the implementation of PMTCT and may have limited early engagement of mothers living with HIV. 114 However without stakeholder engagement, the transition from design and conduct of clinical trials to implementation may not have happened at even slower pace.…”
Section: -97mentioning
confidence: 99%
“…116 A weakness of stakeholder engagement in PMTCT was that civil society leadership comparable for treatment access campaigns had not happened with the same magnitude and failed to engage maternal child health stakeholders from the onset. 114 …”
Section: -97mentioning
confidence: 99%